2008
DOI: 10.1021/jp803989d
|View full text |Cite
|
Sign up to set email alerts
|

Non-oxidizing Purification Method for Large Volumes of Long, Undamaged Single-Walled Carbon Nanotubes

Abstract: A mild route to the purification of single-walled carbon nanotube (SWNT) soot has been investigated. The removal of all forms of impurities commonly found in bulk SWNT material (metal catalyst nanoparticles, amorphous carbon, and bundles of SWNTs) has been obtained. This technique, which involves purification based on centrifugation at low centrifugal force, results in deposits that are composed of individual SWNTs that do not have the defects that result from harsh oxidative treatments. While ultracentrifugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…These impurities often interfere with the desired properties of SWNTs. Therefore, there have been extensive recent investigations into methods of removal of impurities and several highly effective purification techniques: flocculation [94], microfiltration [95,96], chromatographic procedures [97][98][99], and centrifugation [100,101].…”
Section: Mild Routes To Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…These impurities often interfere with the desired properties of SWNTs. Therefore, there have been extensive recent investigations into methods of removal of impurities and several highly effective purification techniques: flocculation [94], microfiltration [95,96], chromatographic procedures [97][98][99], and centrifugation [100,101].…”
Section: Mild Routes To Purificationmentioning
confidence: 99%
“…Many potential applications have been proposed for carbon nanotubes, including conductive, high-strength composites and paint additives. Recent studies have involved the possible applications of SWNTs as nano test-tubes [27,28], H 2 storage media [29,30], batteries [31], field-emission materials [3,29,[32][33][34][35][36][37], tips for scanning probe microscopy [38][39][40][41][42][43][44], chromatographic stationary phases [45,46], transistors [47,48], diodes [49], and sensors [1,22,[50][51][52][53][54][55][56][57][58][59][60][61][62]. SWNTs have interesting physical, morphological and electronic properties and find applications in a variety of areas ranging from biosensors to transistors.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated the complete elimination of graphite particles and the reduction of the amorphous carbon levels by centrifugation in a surfactant [1,2]. Dispersions of increasing SWCNT relative purity can be obtained by repeated centrifugation cycles [3]. Researchers from Flinders University in Australia have systematically studied the enormous possibilities of high speed centrifugation for the preparation of dispersions of purified arc-discharge SWCNTs in aqueous solutions of sodium dodecylbenzene sulfonate (SDBS) [4].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the SWCNTs retained their chemical and physical properties and were not functionalized. In addition, it has been reported that ultracentrifugation, with high centrifugal forces (typically in excess of 100 000 g), could be a nondestructive and non-oxidizing method for CNT purification [33,34]. Recently, Meyer-Plath et al have developed a very fast and entirely gas-phase based plasma-thermal purification technique for CNTs, neither acids nor other chemical reagents were used, and structural integrity of the purified CNTs was preserved [35].…”
Section: Introductionmentioning
confidence: 99%